Chiral-partner D mesons in a heat bath within QCD sum rules. (9th July 2018) - Buchheim, T; Hilger, T; Kämpfer, B; Leupold, S
Abstract: Utilizing QCD sum rules, we extract the temperature dependences of the spectral properties of the pseudo-scalar and scalar D mesons regarded as chiral partners. Besides the masses also decay constants are analyzed as the D meson yields in heavy-ion collisions may be sensitive to their altered decay properties in an ambient strongly interacting medium. Our findings are (i) a decreasing scalar D meson mass for growing temperatures while its pseudo-scalar partner meson seems hardly affected, which is in qualitative agreement with hadronic model calculations; (ii) inferring an equally weak temperature dependence of the pseudo-scalar D meson decay properties the decreasing residua and decay constants of the scalar particle point towards partial chiral restoration. As a bonus of our analysis in the pseudo-scalar sector we determine the pseudo-scalar decay constant at vanishing temperature. Due to the connection to particular leptonic branching fractions this decay constant is of great interest allowing for the determination of the off-diagonal CKM matrix element ∣ V cd ∣ at zero temperature.